Hypoxia Induces Changes in AMP-Activated Protein Kinase Activity and Energy Metabolism in Muscle Tissue of the Oriental River Prawn Macrobrachium nipponense - Sun, Shengming; Gu, Zhongbao; Fu, Hongtuo; Zhu, Jian; Ge, Xianping; Wu, Xugan (Frontiers in Physiology, 2018)
Hypoxia has important effects on biological activity in crustaceans, and modulation of energy metabolism is a crucial aspect of crustaceans’ ability to respond to hypoxia. The adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK) enzyme is very important in cellular energy homeostasis; however, little information is known about the role of AMPK in the response of prawns to acute hypoxia. In the present study, three subunits of AMPK were cloned from the oriental river prawn, Macrobrachium nipponense. The full-length cDNAs of the α, β, and γ AMPK subunits were 1,837 bp, 3,174 bp, and 3,773 bp long, with open reading frames of 529, 289, and 961 amino acids, respectively. Primary amino acid sequence alignment of these three subunits revealed conserved similarity between the functional domains of the M. nipponense AMPK protein with AMPK proteins of other animals. The expression of the three AMPK subunits was higher in muscle tissue than in other tissues. Furthermore, the mRNA expression of AMPKα, AMPKβ, and AMPKγ were significantly up-regulated in M. nipponense muscle tissue after acute hypoxia. Probing with a phospho-AMPKα antibody revealed that AMPK is phosphorylated following hypoxia; this phosphorylation event was found to be essential for AMPK activation. Levels of glucose and lactic acid in hemolymph and muscle tissue were significantly changed over the course of hypoxia and recovery, indicating dynamic changes in energy metabolism in response to hypoxic stress. The activation of AMPK by hypoxic stress in M. nipponense was compared to levels of muscular AMP, ADP, and ATP, as determined by HPLC; it was found that activation of AMPK may not completely correlate with AMP:ATP ratios in prawns under hypoxic conditions. These findings confirm that the α, β, and γ subunits of the prawn AMPK protein are regulated at the transcriptional and protein levels during hypoxic stress to facilitate maintenance of energy homeostasis.